2020
DOI: 10.21303/2504-5571.2020.001535
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Knowledge Management Process on Information and Communication Technology Dimensions and the Contribution of Competitive Advantage in Professors of Physical Education Faculties

Abstract: Today, attention is paid to the importance and special position of information and communication technology (ICT) with the rapid growth of technology that has affected all aspects of organizations in some way and it is one of the components of modern societies. The purpose of this study was to examine the effect of the knowledge management process on ICT dimensions and the contribution of competitive advantage in professors of physical education and sport sciences faculties in Islamic Azad University Branches.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…As an illustration, consider a specific "Leaving Expert Debriefing" in which supervisors, as well as the staff, are examined by colleagues in maintaining the expertise of their specialists that are intending to leave their current business. There were a number of classes within the conference sessions including coaching participatory discussion, and figuring out solutions [6,10,19,22,27].…”
Section: Approaches Of Knowledge Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…As an illustration, consider a specific "Leaving Expert Debriefing" in which supervisors, as well as the staff, are examined by colleagues in maintaining the expertise of their specialists that are intending to leave their current business. There were a number of classes within the conference sessions including coaching participatory discussion, and figuring out solutions [6,10,19,22,27].…”
Section: Approaches Of Knowledge Managementmentioning
confidence: 99%
“…Although there are many different ideas on knowledge management, most people agree that information technology is a crucial part of KM. As a matter of fact, solid computer systems and technology are widely cited as the cornerstone of knowledge management (KM) [10,11,21,28,30]. As a result, implementing technology systems is a crucial component that can be added to KM activities.…”
Section: Approaches Of Knowledge Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Cost reduction is the principal organizational objective of competitive companies (Rahim et al, 2019). They even want to cost low prices of the goods manufactured by firms that operate on competition boundaries (Kalashi et al, 2020). Management operations aim to reduce manufacturing costs against rivals and achieve sustainable pricing that improves goods' competitive advantage (Hurmelinna-Laukkanen et al, 2018).…”
Section: Costmentioning
confidence: 99%
“…More concretely, scholarly studies have revealed that intelligent and knowledgeable employees are key organizational resources. Along with creativity, innovation, and the persistent designment of organizational processes and leading technologies, these kind of employees allow businesses to develop leading market positions [16]. In addition, scholars have argued that the relationship between knowledge management and competitiveness' level or business sustainability, implies that knowledge management represents a crucial strategic asset, as it contributes to the increment of performance via employee's interaction and knowledge exchange.…”
Section: Job Performance and Knowledge Managementmentioning
confidence: 99%